2020
DOI: 10.1038/s41467-020-16159-y
|View full text |Cite
|
Sign up to set email alerts
|

Single cell transcriptomics reveals opioid usage evokes widespread suppression of antiviral gene program

Abstract: Chronic opioid usage not only causes addiction behavior through the central nervous system, but also modulates the peripheral immune system. However, how opioid impacts the immune system is still barely characterized systematically. In order to understand the immune modulatory effect of opioids in an unbiased way, here we perform single-cell RNA sequencing (scRNA-seq) of peripheral blood mononuclear cells from opioid-dependent individuals and controls to show that chronic opioid usage evokes widespread suppres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Worldwide, it is estimated that 80% of injection drug users take opioids, and 17.8% of them are HIV positive ( 4 , 5 ). Epidemiological studies have shown that chronic opioid administration is immunosuppressive, downregulates the antiviral genes, and increases the susceptibility to infections such as tuberculosis and HIV ( 6 12 ). The innate and adaptive immune responses act in synchrony against the invading pathogens, and opioids acting through the opioid receptors alter both these responses ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, it is estimated that 80% of injection drug users take opioids, and 17.8% of them are HIV positive ( 4 , 5 ). Epidemiological studies have shown that chronic opioid administration is immunosuppressive, downregulates the antiviral genes, and increases the susceptibility to infections such as tuberculosis and HIV ( 6 12 ). The innate and adaptive immune responses act in synchrony against the invading pathogens, and opioids acting through the opioid receptors alter both these responses ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following LPS stimulation, PBMCs from individuals with chronic opioid use, and PMBCs from healthy individuals treated with morphine in vitro demonstrated reduced interferon-stimulated gene and antiviral gene expression compared to untreated healthy control PBMCs. This effect was observed in all identified cell subsets including monocytes, CD4 + T cells, CD8 + T cells, B cells, and NK cells [ 136 ]. Interestingly, morphine treatment of hepatocytes has also been associated with reduced IFN-α production and enhanced HCV replication in vitro [ 137 ].…”
Section: Understanding Vaccine Immunogenicity In Populations Most At Risk For Hcvmentioning
confidence: 99%
“…Next-generation sequencing technologies such as RNA-sequencing have become standard for querying gene expression in tissues and cells 24 . Gene expression patterns in bioinformatics data sets help provide information about expression differences, relevant clinical features and functions, and clinical outcomes related to these genes.…”
Section: Introductionmentioning
confidence: 99%